Pneumococcal vaccination in older adults – useful, but underused weapon - Filipić, Brankica (Archives of Pharmacy, 2025)
Streptococcus pneumoniae is a Gram-positive coccus with a characteristic oval shape, microscopically most often grouped in pairs (diplococci). It is encapsulated microorganism responsible for a variety of infections in humans, which can be categorized into non-invasive and invasive forms. Although pneumococcal conjugate vaccines (PCVs) and the 23-valent pneumococcal polysaccharide vaccine (PPSV23) are widely recommended for routine use in older adults and adults with underlying conditions across many countries, infections caused by S. pneumoniae continue to impose a major burden on patients and healthcare systems, and invasive diseases can leave neurological consequences and have a fatal outcome. Key challenges include infections caused by serotypes not present within vaccines and suboptimal vaccination coverage among older adults, even in developed countries. PCVs differ from PPSV23 as capsular polysaccharides are conjugated with a carrier protein, while PPSV23 contains 23 purified capsular polysaccharides. In addition, an important difference between PPSV23 and PCVs is that PPSV23 induces T-cell independent humoral immune response, while, in contrast, conjugate vaccines induce T-cell dependent immune response leading to the formation of specific antibodies and memory B-cells. The pneumococcal vaccination schedule recommended for adults aged between 19 and 64 and those over the age of 65 depends on chronic medical conditions. In 2021, the United States approved two new vaccines, PCV15 and PCV20, while in 2024, the Food and Drug Administration approved PCV21 for adult use. Despite available vaccines, vaccination coverage in adults remains low, indicating that vaccination, as the most crucial preventive measure, is not being applied sufficiently. To raise awareness of adult vaccination, educational campaigns providing evidence-based information addressing misinformation about vaccines and actively involving healthcare workers in primary care settings to promote vaccination are also essential.
Keywords: pneumococcal vaccine; older adults; conjugate vaccines; polysaccharide vaccine